(untitled) (Research, Society and Development, 2025)
In Brazil there are medicinal plants with the vernacular name of ´´cidreira´´ belonging to different families and plant species, popularly used as tranquilizers with potential use for the Unified Brazilian Health System (SUS). Many are sold dehidrated, named as vegetable drugs, in commercial food establishments and quality controls on these products are scarce. This investigation aims to Analyse the quality of plant medicines marketed under the name “cidreira” in Western Paraná. The pharmacognostic quality analyzes recommended by the Brazilian Pharmacopeia VI were carried out on 15 (fifteen) samples of “cidreira” obtained randomly in the Cascavel-PR market. Botanical identity tests, chromatographic chemical profile, purity tests (foreign matters, loss on drying, total ashes) and dosage of volatile oils were applied and compared with the established parameters and standards of the four groups of plant species investigated and duly identified. All commercial samples evaluated failed in terms of quality. One of the samples presented a mistaken identity, not being M. officinalis but L. alba. The foreign matter tests (53%), loss due to drying (92%) indicated that the majority of the samples evaluated presented values ​​above the established limits, while the ash content, only 7% presented values ​​above the limits. Regarding the content of volatile oils, 100% of the samples were below the minimum required. According to the pharmacognostic tests carried out, all samples presented lower quality than that recommended by the Brazilian Pharmacopoeia, indicating the need for greater control in the processing of marketed plant drugs.